71.0k views
0 votes
Find the answer for x and for y
y=4x-3
8x+2y=-6

2 Answers

6 votes
The first equation is already solved for y, so substitute in the second equation.

8x + 2(4x - 3) = -6

8x + 8x - 6 = -6

16x = 0

x = 0

y = 4x - 3

y = 4(0) - 3

y = -3

Answer: x = 0 and y = -3
User Lamon
by
5.6k points
4 votes
y = 4x - 3

8x + 2y = -6

8x + 2(4x - 3) = -6
8x + 8x - 6 = -6
16x - 6 = -6
16x -6(+6) = -6 (+6)
16x = 0
16x/16 = 0/16
x = 0


y = 4x - 3
y = 4(0) -3
y = 0 - 3
y = -3

x = 0, y = -3 is your answer

hope this helps
User Dgp
by
4.7k points